Perumusan Rencana Strategis Sekolah Berbasis Analisis SWOT dalam Meningkatkan Mutu Pendidikan: Studi Kasus SMP Negeri 7 Samarinda - Catur Prida Retnivia; Pratisa Martha Sari; Krista Alisa Meyliani; Intan Beauty Kusnukiandany; Ramadiani Ramadiani; Sudarman Sudarman (Manajemen Pendidikan Program Doktor, 2026)
Strategic planning is a fundamental component of school management that provides direction for sustainable educational development and quality improvement. This study aims to develop a School Strategic Plan (RENSTRA) for SMP Negeri 7 Samarinda for the 2026–2031 period based on a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. The research employed a qualitative case study approach. Data were collected through observations, semi-structured interviews, documentation, and literature review. Data analysis followed the Miles, Huberman, and Saldaña interactive model, while strategic formulation was conducted using the IFAS, EFAS, and SWOT matrices. The findings indicate that SMP Negeri 7 Samarinda possesses significant strengths, including an A accreditation, well-established flagship programs such as an inclusive school, Adiwiyata School, and Population-Aware School (SSK), as well as adequate educational facilities and human resources. However, several challenges remain, including the need to enhance teachers' digital competencies, strengthen inclusive education services, and modernize school management. External opportunities, such as national education transformation policies, digital technology advancement, and strategic partnerships, provide considerable potential for school development despite increasing competition and rapid technological change. Based on the SWOT analysis, eight strategic priorities were formulated, covering academic quality improvement, character education, school digitalization, student achievement, environmental sustainability, teacher professional development, infrastructure modernization, and governance enhancement. These priorities were translated into measurable strategic objectives, key performance indicators, annual targets, and a five-year implementation roadmap. The novelty of this study lies in integrating SWOT analysis with a comprehensive strategic roadmap that includes measurable performance indicators and implementation targets, resulting in a practical and evidence-based strategic planning framework. The proposed model is expected to support sustainable school improvement and serve as a reference for other schools in developing strategic plans aligned with national education transformation policies.